Attitudes, Difficulties and Strategies in Learning English Idioms: A Case Study of EFL Students at Ghor University - Sakhi Murad Ghorianfar; Nesar Ahmad Wahedi; Asadullah Faizy (LinguaEducare: Journal of English and Linguistic Studies, 2026)
Idioms are an important part of learning English vocabulary and fluency; however, they are often overlooked in EFL classrooms, especially where language instruction focuses on grammar and literal vocabulary. This study examined the attitudes of EFL students at Ghor University toward learning idioms, the difficulties they faced, and the strategies they used. To achieve the research objectives, a descriptive research design was employed. Data were collected from 78 EFL students using a questionnaire and analyzed using SPSS version 26. The results indicated that students held a positive attitude toward the importance of learning idioms but faced difficulties such as unfamiliar words, inadequate classroom instruction, ineffective cultural courses, the absence of direct equivalents in Farsi, and limited experience in using them. To overcome these challenges, they used strategies like translating idioms into Farsi, using keywords, practicing English outside class, and guessing meanings from context. The study suggests that EFL instructors in similar contexts could integrate idioms into classroom activities using interactive and practical strategies to support learning. However, these findings provide a useful insight into the experiences of students at a single institution and may not be generalizable to other contexts. Therefore, any teaching suggestions should be considered carefully.